The Role Of Digital Economy As A Booster For Increasing Labor Employment And MSMEs Income In Surabaya City - Aulia Paramastuti*, Anindita (Riwayat: Educational Journal of History and Humanities, 2024)
This research aims to determine the role of the digital economy and labour absorption in encouraging an increase in MSMEs income in Surabaya. By taking data from 100 MSMEs in the town of Surabaya using a purposive sampling technique, this research created a survey instrument, which was then processed through descriptive analysis. The research results concluded that the digital economy and employment have a role in increasing the income of MSMEs in Surabaya.Thisprovides evidence that The digital economy has provided great opportunities for creating new jobs, which impacts workforce absorption. The use of digital technology can affect the amount and level of production, which indirectly provides opportunities for labour demand.